Reforming German labor market institutions: a dual path to flexibility - Werner Eichhorst; Paul Marx (Institute for the Study of Labor (IZA), 2009)
Germany has always been one of the prime examples of institutional complementarities between social insurance, a rather passive welfare state, strong employment protection and collective bargaining that stabilize diversified quality production. This institutional arrangement was criticized for being the main cause of inferior labor market performance and increasing fiscal pressure on the welfare state while at the same time inhibiting institutional change. However, over the last 15 years, a sequence of institutional reforms has fundamentally modified the functioning of the German labor market and increased both flexibility and job creation capacities through two intimately linked processes that redefined the line between inactivity, the flexible and the standard segment of the labor market. On the one hand, policy changes facilitated the expansion of flexible or 'atypical' jobs, whereas increasing flexibility of the standard employment relationship resulted from wage moderation and working time flexibility. While at the outset of this reform sequence German had a small, but relatively egalitarian labor market, the number of jobs, but also their diversity has increased.
urn:nbn:de:101:1-20090403134
Keywords: J38; J51; J41; 330; Germany; labor market reforms; atypical employment; standard employment relationship; Arbeitsmarktpolitik; Reform; Arbeitsmarktflexibilisierung; Wirkungsanalyse; Beschäftigungseffekt; Arbeitsverhältnis; Ungeschützte Beschäftigung; Deutschland